Numerical simulation of air–water two–phase flow in vertical pipe using k-ε model - Sanati, Ali (International Journal of Engineering and Technology, 2015)
Two-phase flow exists mostly in pipes and is of substantial importance in pipeline industry. Numerical data are presented in this paper for water and air velocity in two-phase flow through vertical circular channel using both K-ε model and empirical correlations. In order to investigate the pressure distribution for various flow conditions, two-phase flow was considered through two vertical pipes with different lengths and the same diameters. Moreover, we studied flow entering from below and getting out from top of the pipe. Results obtained in this study have been analyzed with experimental data, showing that the average void fraction rises with increasing inlet gas velocity and drops with increasing inlet water velocity. Also results show that Hassan & Kabir method is the most appropriate approach in comparison with the others.